Factores críticos de éxito de las empresas innovadoras: una investigación documental (Critical success factors of innovative companies: documentary research) - Avila Hernández, Laura Elizabeth; Alarcón Martinez, Gustavo Juan (Facultad de Contaduría Pública y Administración U.A.N.L., 2014)
Abstract. This article is a documentary research on the critical success factors of innovative companies. Regarding this, several definitions of innovative companies are presented, as well as the nature and focus of innovation in companies. Subsequently, conceptual models developed by outstanding authors for innovative companies are mentioned. Finally common elements found in literature review in these investigations are described as critical success factors of innovative companies, namely: strategic leadership for innovation; multifunctional teams for innovation; recognition system for business innovation; technological process for developing new products and process; analysis of markets for new products or services; investment in research and development.